RESEARCH OF THE INFLUENCE OF PEN FLEXIBILITY ON OPTIMUM REQUIREMENTS LINKINGS OF SHELVES PAIRWISE SHROUDED BLADES OF TURBINES - Анатолій Павлович Зіньковський; Вячеслав Михайлович Меркулов; Іван Гордійович Токар; Олег Леонідович Деркач; Руслан Юрійович Шакало (Авіаційно-космічна техніка та технологія, 2020)
In the article outcomes of probes by definition of influencing the flexibility of pen on optimum requirements of linking of shelves pairwise shrouded blades of turbines are considered. A design feature of such blades is that a composite shank, each half of which has a pen with a bezigless shroud platform, is freely inserted into the groove of disk. The application examples pairwise shrouded blades in turbines of a gas turbine engine (GTD), and also outcomes of the analysis of initial conditions of linking on shroud platforms of such blades are set up. It is shown that under the conditions of operation of the engine, there can be both an interference fit and a clearance on the shroud platform. A description is given of the developed methods for the experimental determination of the initial conditions for pairing the retaining shelves of pairwise shrouded blades and the study of their damping ability and vibration stress. Outcomes of the analysis of requirements of linking of bandage shelves of blading of impellors, experimental researches by definition of their influencing on vibrational stresses and a damping current capacity pairwise shrouded blades and their beam models as systems with a rigorous regular which one is characterized by the elastic-dissipative connection caused both bandages, and tool joints, taking into account flexibility of pen are introduced. It is displayed, that there is the best value of the argument of linking of bandage shelves at which one the maximum damping current capacity of twin blades and according to their minimum of vibrational stresses is reached. Thus, its meaning depends on the flexibility of the pen of a blade. By results of the conducted experimental researches of packages of pairwise shrouded blades of three turbine stages GTD AI-25 and turbine GTD D-36 first stage the relation of the best value of argument Δн, wholesale of linking of bandage shelves from the flexibility of pen which one allows to forecast its value for blades of other stages GTD is constructed. As blades of first stages of turbines GTD AI-322 and D-36 are characterized by flexibility neighbors it is possible to forecast with a high probability, that best values of the argument of linking of their shroud platforms will be one level.